ANALISIS EFEKTIVITAS SISTEM IRIGASI TETES PADA KOMODITI TANAMAN TOMAT (Solanum Lycopersicum L.)DI PT AGROMAR - Avelino Nurak, Frederik; Nong, Fiator; Iawan Saputera Wanda, Taras (Universitas Cokroaminoto Palopo, 2025)
This research aims to analyze the effectiveness of the drip irrigation system on tomato crops using qualitative data analysis methods. This research presents findings regarding efficient water use, increasing plant productivity, and disease control, related to the application of the drip irrigation system on tomato plants. The results of the research provide a positive picture regarding the effectiveness of this technology. The aim of this activity is to determine the effectiveness of the drip irrigation system on tomato crops. It is hoped that this activity can provide a sustainable positive impact for PT farmers. Agromar and increasing public awareness of using drip irrigation technology in tomato farming businesses at PT. Agromar